Heterozygous Single-Nucleotide Polymorphism Genotypes at Heat Shock Protein 70 Gene Potentially Influence Thermo-Tolerance Among Four Zebu Breeds of Nigeria - Onasanya, Gbolabo Olaitan; Msalya, George Mutani; Thiruvenkadan, Aranganoor Kannan; Sreekumar, Chirukandoth; Tirumurugaan, Gopalan Krishnaswamy; Fafiolu, Adeboye O.; Adeleke, Matthew A.; Yakubu, Abdulmojeed; Ikeobi, Christian Obiora Ndubuisi; Okpeku, Moses (Frontiers in Genetics, 2021)
Genetic variants at heat shock protein (HSP) 70 gene and their influence on heat stress (HS) tolerance were studied among selected Nigeria zebu, namely; 25 White Fulani (WF), 21 Sokoto Gudali (SG), 21 Red Bororo (RB), and 23 Ambala (AM). Single nucleotide polymorphisms (SNPs) detection followed by genotypes and genotypic frequencies determination were made among the selected breeds. Heat tolerance coefficient (HTC) was determined from thermo-related parameters including, body temperature, rectal temperature, and respiratory rate and the thermo-tolerance was evaluated through SNPs-thermo-parameters relationship. Statistical analyses were done using GLM procedure in SAS. Qreal time/high resolution melting based assay detected twelve genetic variants and five of these were common and shared across all breeds of cattle. Of the remaining seven variants, three were specifically identified in Ambala, two in Sokoto Gudali, and two in Red Bororo. Four unique SNPs (C151T, C146T, G90A, and C219A) were identified. Heterozygous animals had lower HTC suggesting their potential to withstand HS than homozygous counterparts. Thermo-related parameters were significantly different (P<0.001) and recommended that the screening of SNPs in zebu may be made for early selection for improved thermo-tolerance.